1983
DOI: 10.1111/j.1432-1033.1983.tb07490.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pyruvate Dehydrogenase Complex of Escherichia coli K12

Abstract: The nucleotide sequence of the aceF gene, which encodes the dihydrolipoamide acetyltransferase component (E2) of the pyruvate dehydrogenase complex of Escherichia coli Kl2, has been determined using the dideoxy chaintermination method. The aceFgene comprises 1887 base pairs (629 codons excluding the initiation codon AUG); it is preceded by a short intercistronic segment of 14 base pairs containing a good ribosomal binding site, and it is followed closely by a potential rho-independent terminator. The results e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
101
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(110 citation statements)
references
References 49 publications
8
101
1
Order By: Relevance
“…The E2 subunit forms the core to which all other PDC subunits bind (10). In Gram-negative bacteria such as Escherichia coli, the oligomeric core contains eight E2 trimers arranged as a cube with octahedral symmetry (11), while in Gram-positive bacteria (12,13) and eukaryotes (14,15) the core contains 20 E2 trimers arranged as a pentagonal dodecahedron with icosahedral symmetry. Amino acid sequence alignments comparing E2s from divergent organisms revealed that they are multi-domain proteins (see Ref.…”
mentioning
confidence: 99%
“…The E2 subunit forms the core to which all other PDC subunits bind (10). In Gram-negative bacteria such as Escherichia coli, the oligomeric core contains eight E2 trimers arranged as a cube with octahedral symmetry (11), while in Gram-positive bacteria (12,13) and eukaryotes (14,15) the core contains 20 E2 trimers arranged as a pentagonal dodecahedron with icosahedral symmetry. Amino acid sequence alignments comparing E2s from divergent organisms revealed that they are multi-domain proteins (see Ref.…”
mentioning
confidence: 99%
“…[3][4][5]. The thiamin diphosphate (ThDP)-dependent E1 component (E1ec, pyruvate dehydrogenase) is an ␣ 2 homodimer and carries out consecutively pyruvate decarboxylation and reductive acetylation of the E2 component (Equation 3).…”
mentioning
confidence: 99%
“…Such reconstitutions, carried out mainly with the E. coli complex, have been instrumental in demonstrating the existence of a high-molecular-weight core particle composed of KE2 onto which are attached dimeric units of KE1 and E3 (18,31). Knowledge of the primary structures of the components of KGDC (4,5,28) and the pyruvate dehydrogenase complex (PDC) (15,29,30), gained from the cloned genes, has contributed new insights about the domains involved in catalytic activity and subunit interaction (16,17,36).…”
mentioning
confidence: 99%
“…Such reconstitutions, carried out mainly with the E. coli complex, have been instrumental in demonstrating the existence of a high-molecular-weight core particle composed of KE2 onto which are attached dimeric units of KE1 and E3 (18,31). Knowledge of the primary structures of the components of KGDC (4, 5, 28) and the pyruvate dehydrogenase complex (PDC) (15,29,30), gained from the cloned genes, has contributed new insights about the domains involved in catalytic activity and subunit interaction (16,17,36).Despite the large body of information bearing on structure and function relationships in KGDC and PDC, little attention has been paid in the past to the mechanisms ensuring a coordinate expression of their constituent enzymes and the * Corresponding author. manner in which they interact with one another in vivo to form the functional complexes.…”
mentioning
confidence: 99%